2018
DOI: 10.1016/j.ygcen.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Group housing during adolescence has long-term effects on the adult stress response in female, but not male, zebra finches (Taeniopygia guttata)

Abstract: HighlightsAdolescent group size, not density, influences adult corticosterone secretion.A larger group size results in higher corticosterone secretion during restraint.The adolescent group size effects on corticosterone were only found in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Hence, one month after transfer, the hormonal phenotype of colony-housed males was changed towards that of pair-housed males. Enduring changes in HPA axis function due to social conditions have been already reported in other vertebrates during earlier phases of life: in zebra finches, for example, group housing during adolescence had long-term effects on adult HPA responsiveness in females [56].…”
Section: Discussionmentioning
confidence: 59%
“…Hence, one month after transfer, the hormonal phenotype of colony-housed males was changed towards that of pair-housed males. Enduring changes in HPA axis function due to social conditions have been already reported in other vertebrates during earlier phases of life: in zebra finches, for example, group housing during adolescence had long-term effects on adult HPA responsiveness in females [56].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown that high‐density crowding would shortens the life‐span of D. melanogaster [ 17 ] and Zebra finches; [ 33 ] however, but such observations are lacking in mammals. In the present study, we found that high housing density significantly shortened the lifespan of Brandt's voles.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, wildcaught babblers held captive for a few days for an adrenocorticotropic hormone challenge validating fGCMs as a proxy for circulating GCs had 50-fold higher fGCM concentrations compared with free-ranging conspecifics (Jepsen et al 2019). Captivity-induced stress is typically a response to factors including the capture event itself, transport and handling (Nilsson et al 2008;Dickens et al 2009), and exposure to an unnatural environment (e.g., artificial light and noise and a general lack of stimulation or appropriate social housing; Young 2003; Morgan and Tromborg 2007;Calisi and Bentley 2009;Emmerson and Spencer 2018).…”
Section: Discussionmentioning
confidence: 99%